The effectiveness of group therapy of emotions regulation on symptoms of women with borderline personality disorder - Mirzaie, Amir; Sharifi, Tayebe; Ghazanfari, Ahmad; Chorami, Maryam (Applied Family Therapy Journal (AFTJ), 2021)
Aim: This study was aimed to determine the effect of group therapy of emotion regulation on the symptoms of women with a borderline personality disorder. Methods: This study was quasi-experimental with a pretest-posttest design and follow-up with experimental and control groups. The study population of this study included 50 women with boundary personality disorder referring to the Tohid psychology clinic in Isfahan. After screening the population with the Personality Questionnaire of Listerning (1999) and the borderline personality of Jackson and Claridge (1991), 18 females were selected as the study sample by the purposive sampling method and were randomly assigned to an experimental group (9 women) and a control group (9 women). In this study, the experimental group received eight sessions of the emotion regulation model of Gras (2003) and each session lasted 90 minutes. The repeated-measures analysis of variance was used to analyze the data. Results: The findings indicated that the emotion regulation is effective on the symptoms of emotional turmoil (F = 13.00, p = 0.001), disappointment (F = 31.25, P = 0.001), fear of intimacy (F = 52.30, P = 0.001) and impulsivity (F = 71.58, p = 0.001). Also, this impact was stable in the follow-up stage as well. Conclusions: The results indicated that it is better to use group therapy to improve the condition of women with borderline personality disorders.